Significant Hematochezia and Intracranial Bleeding in Neonatal Hereditary Hemorrhagic Telangiectasia - Merves, Matthew; Parsons, Kimberly; Alazraki, Adina; Meisel, Jonathan; Sauer, Cary; Li, Hong (American Journal of Perinatology Reports, 2019)
Hereditary hemorrhagic telangiectasia (HHT) is an underreported autosomal dominant vascular dysplasia. Neonatal presentations of HHT are rare, as this disorder typically presents in adolescence or beyond with epistaxis. We report a female neonate with hematochezia on the 1st day of life secondary to multiple gastrointestinal arteriovenous malformations (AVMs) along with intracranial hemorrhage. We describe her clinical course and management, as well as her novel family mutation in ENG. This is the first reported HHT case with significant gastrointestinal bleeding in the newborn. We review neonatal HHT and raise the consideration for more directed prenatal imaging and delivery options for fetuses at high risk of HHT.
Keywords: hereditary hemorrhagic telangiectasia; Osler–Weber–Rendu syndrome; hematochezia; intracranial bleeding; neonate